A new genus of river snails, Bakyietaia (Mollusca, Viviparid Ae), from South China and the Indochinese Peninsula - Le-Jia Zhang; Yu-Hsiu Yen; Zhe-Yu Chen; Li-Na Du; Ting Hui Ng; Thomas von Rintelen (European Journal of Taxonomy, 2025)
A new genus of the river snail family Viviparid Ae, Bakyietaia Zhang, Yen & von Rintelen gen. Nov., is described based on a comprehensive study of its morphology, anatomy, mtDNA (COI), ecology and distribution. This genus is widely distributed in South China and the Indochinese Peninsula. It can be distinguished from all other viviparid genera, especially Angulyagra, Sinotaia and Anulotaia, by characters of the columellar lip of the shell, the operculum and the marginal teeth of radula. Based on an integrative taxonomic approach, 17 species are assigned to this new genus and described here, including 7 new combinations and 10 new species: Bakyietaia subcostata gen. et comb. nov., B. polyzonata gen. et comb. Nov., B. boettgeri gen. et comb. nov., B. duchieri gen. et comb. nov., B. guangdungensis gen. et comb. nov., B. mutica gen. et comb. nov., B. wilhelmi gen. et comb. nov., B. chenghuang Zhang, Yen & von Rintelen gen. et sp. nov., B. jingweiae Yen, Zhang & von Rintelen gen. et sp. nov., B. liusanjieae Zhang, Yen & von Rintelen gen. et sp. nov., B. avisvenatoris Yen, Zhang & von Rintelen gen. et sp. nov., B. liangzhuorum Yen, Zhang & von Rintelen gen. et sp. nov., B. luikongi Yen, Zhang & von Rintelen gen. et sp. nov., B. fontinalis Zhang, Yen & von Rintelen gen. et sp. nov., B. naiadica Zhang, Yen & von Rintelen gen. et sp. nov., B. luuemxlong Zhang, Yen & von Rintelen gen. et sp. nov. and B. indrapura Zhang, Yen & von Rintelen gen. et sp. nov. The monophyly of all morphospecies is supported by the COI phylogeny. Radular characters, especially the number of cusps of the outer marginal teeth, are considered valuable in the classification of species of Bakyietaia with similar shells.